Elbow joint kinematics during cricket bowling using magneto-inertial sensors: A feasibility study - Wells, D.; Alderson, J.; Camomilla, V.; Donnelly, C.; Elliott, B.; Cereatti, A. (Journal of Sports Sciences, 2019)
Magnetic and inertial measurement units (MIMUs) may provide an accessible, three-dimensional, in-field alternative to laboratory-restricted marker-based motion capture. Existing upper limb MIMU models have predominantly been validated with low-velocity motion and their suitability for use with sport-based movements remains relatively untested. We propose a MIMU system approach to enable the estimation of anatomically meaningful and participant-specific elbow kinematics with considerations for use with cricket bowling. A novel standardised elbow reference posture of 90 degrees flexion and 0 deg pronation, and functional definition of elbow joint axes of rotation calibrated the MIMU method model before it was validated across three experiments: (1) simple elbow rotations with a mechanical linkage; (2) low-velocity elbow rotations in human participants; and (3) low-medium velocity sport-based movements in human participants. The proposed MIMU method demonstrated high elbow kinematic measurement agreement when compared with a criterion measure across all three conditions. However, during experiment 3, sensor components neared their measurement capacity and the MIMU method elbow flexion measurement variability increased. We conclude that the proposed MIMU method can estimate anatomically referenced, participant-specific joint angles, however, the hardware specifications of currently available systems may limit application in high-velocity/acceleration situations, preventing the measurement of cricket bowling in-field for now.